The Impact of The Digital Economy on Macroeconomic Growth and Stability Post-Pandemic for Society - Kharinatul Hanani (International Journal of Economics, Science, and Education, 2025)
The COVID-19 pandemic has catalyzed the acceleration of the digital economy globally. Mobility restrictions and disruptions to conventional economic activities have forced governments, businesses, and the public to rapidly adopt digital technology. This article aims to analyze the impact of the digital economy on economic growth and macroeconomic stability during the pandemic. The method used is a library study, examining academic literature, reports from international institutions, and policy publications related to the digital economy and the pandemic. The study's results indicate that the digital economy plays a crucial role in maintaining economic growth amidst the global contraction by increasing productivity, sustaining business activity, and promoting digital financial inclusion. However, the "forced" acceleration of digitalization also creates new risks to macroeconomic stability, particularly in the employment sector, income inequality, and financial system stability. Therefore, adaptive macroeconomic policies and digital regulations are needed to ensure the sustainability of the digital economy's benefits during the crisis.